Analysis of the Effectiveness of Waqf Policy Management for Tafakulink Salam Products at PT Tafakul Keluarga, Medan Branch, in Accordance with the Fatwa of DSN MUI Number 106 of 2016 (Jurnal Manajemen Bisnis, 2024)
Waqf in Islamic insurance, especially in products like Takafulink Salam, exhibits significant differences from conventional waqf, which typically involves the preservation of buildings or land by past communities. The research aims to analyze the role of waqf in Sharia-compliant insurance products and to comprehend the concept of waqf as a worship and social instrument in the context of Sharia insurance. The research methodology involves in-depth interviews and documentation techniques focusing on the waqf pledge within Sharia life insurance policies, fee provisions within policies, and other aspects regulated by relevant regulations and fatwas. The research findings indicate that waqf pledges are made on various occasions, such as the end of the agreement period, redemption by policyholders, or the death of the main participants. Financial aspects, including fees, are regulated by the Financial Services Authority Regulation (POJK) Number 69/POJK.05/2016. Fatwa DSN No.52/DSN-MUI/III/2006 provides guidelines regarding the contract of agency with a fee in Sharia insurance. The research concludes by emphasizing the important role of waqf in Sharia insurance, creating social and worship benefits, and illustrating the integration of waqf in Sharia insurance products such as Takafulink Salam. Although related to insurance, the concept of waqf remains distinct as a form of worship that supports social development.